Inpatient Rehabilitation: Prediction of Changes in Sensorimotor Performance in Multiple Sclerosis: A Pilot Study - Gulde, Philipp (J Clin Med, 2021)
Inpatient rehabilitation has been shown to be an effective intervention for sensorimotor performance in multiple sclerosis (MS) patients. So far, predictions of the rehabilitation outcomes are limited. The objective was to predict inpatient rehabilitation outcomes by changes in the Watzmann Severity Scale (WSS), a statistical estimation of the EDSS by sensorimotor capacity. Sensorimotor performance and physical activity during rehabilitation (by actigraphy) were assessed in a sample of 28 MS patients at a facility for neurorehabilitation. Daily changes in the WSS were predicted by a model of multiple linear regression. The resulting model had an R(2)(adjusted) of 0.48 (p < 0.01) and revealed five impacting factors (a reduction in the WSS represents an improvement): the number of steps (β-weight = 0.52, p < 0.01), the duration of nocturnal rest time (β-weight = 0.46, p = 0.01), the EDSS at entry (β-weight = 0.38, p = 0.03), a relapsing-remitting MS (β-weight = 0.37, p = 0.03), and the performance in a visuomotor pursuit task with time pressure (β-weight = −0.35, p = 0.04). One standard deviation improvement was predicted when the patient at admission yielded 6600 fewer steps per day, 94 min less rest per night, −2.7 points in the EDSS at entry, a relapsing-remitting MS, and a pursuit task performance that decreased by 2.2 standard deviations. Overall, the patients improved by −0.22 ± 0.51 WSS points during 19.3 ± 4.5 d of inpatient rehabilitation. Different potential explanations of the findings are discussed, one of which proposes that the results reflect an unhealthy lifestyle which, in addition to MS, would explain the higher predicted improvements by rehabilitation tackling both MS and the patients’ lifestyle.